ANALISIS KINERJA KEUANGAN PADA CAHAYA LAUNDRY - Frans Tulaseket; Longginus Gelatan (ADMIN: Jurnal Administrasi Negara, 2023)
The purpose of this research is to analyze the financial performance of Cahaya Laundry. The type of data used is quantitative and qualitative data. Data collection techniques in research are documentation and interviews. The analytical tools used are profitability ratios (ROA and ROE) and liquidity ratios (current ratio). The results of this study indicate that Cahaya Laundry's financial performance in terms of profitability ratios, namely Return On Assets in the 2019 period was 0.54% and decreased in the 2020 period by 0.37%, Return On Equity in the 2019 period was 0.53% and decreased in the 2020 period by 0.36%. The liquidity ratio, namely the Current Ratio in 2019 was 904% and increased in 2020 by 1.437%.